Pelatihan Teknik Komunikasi Total bagi Guru dan Orang Tua dalam Meningkatkan Kemampuan Bahasa Anak Tunagrahita Ringan di SLBN Pembina Kupang - Markus Sampe; Rista Apriliya Devi (Prodi PGSD Unsultra, 2025)
The language skills of children with mild intellectual disabilities often experience obstacles due to limitations in intellectual function and social adaptation. One approach that can help the communication process of children with mild intellectual disabilities is the total communication technique, which is a method that combines various forms of communication such as verbal, nonverbal, sign language, visual, and body language. This community service activity aims to improve the understanding and skills of teachers and parents in implementing total communication techniques to support the language development of children with mild intellectual disabilities at SLBN Pembina Kupang. This activity was carried out for three days and involved 15 teachers and 20 parents of students. The implementation method included interactive lectures, demonstrations of total communication techniques, practical simulations in the context of everyday life, as well as mentoring and evaluation sessions. The results of the activity showed an increase in the average understanding of participants from 56% to 85% based on the pretest and posttest. In addition, participants showed better practical skills in using simple sign language, facial expressions, and visual aids. Teachers felt more confident in delivering lessons to students, while parents felt more able to establish meaningful communication with their children. This activity has a positive impact and can be replicated in other schools with similar conditions